2017
DOI: 10.1080/0142159x.2017.1396306
|View full text |Cite
|
Sign up to set email alerts
|

Twelve tips to promote successful development of a learner performance dashboard within a medical education program

Abstract: Easily accessible and interpretable performance data constitute critical feedback for learners that facilitate informed self-assessment and learning planning. To provide this feedback, there has been a proliferation of educational dashboards in recent years. An educational (learner) dashboard systematically delivers timely and continuous feedback on performance and can provide easily visualized and interpreted performance data. In this paper, we provide practical tips for developing a functional, user-friendly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 18 publications
1
55
0
1
Order By: Relevance
“…The current lack of systematic procedures for evidentiary review, weighting and interpretation and the heterogeneity of practices within committees have been problematised . In response, a variety of strategies have been proposed to standardise CCCs, including best operating practices, faculty training, data visualisation software and data analysis programs …”
Section: Introductionmentioning
confidence: 99%
“…The current lack of systematic procedures for evidentiary review, weighting and interpretation and the heterogeneity of practices within committees have been problematised . In response, a variety of strategies have been proposed to standardise CCCs, including best operating practices, faculty training, data visualisation software and data analysis programs …”
Section: Introductionmentioning
confidence: 99%
“…We utilized a design-based research approach [24][25][26] and followed best practices 23,26,27 to meet this objective. We report the qualitative components of our project in keeping with the consolidated criteria for reporting qualitative research.…”
Section: Methodsmentioning
confidence: 99%
“…17,22 The development of such dashboards is an iterative process 18 and requires collaboration with information technology experts, assessment experts, data managers, and dashboard users. 23…”
Section: Introductionmentioning
confidence: 99%
“…7 Data visualisation involves the creation and study of data that have been abstracted, summarised or categorised in some schematic form. 7,8 It combines data from various assessments to organise and visualise data for interpretation, and is employed to effectively provide feedback to students and to assist faculty members in making competency-based decisions. 4,6 The data visualisation can provide efficient feedback, yet Hauer and colleagues found that students' use of this information to guide learning is variable: some students engaged in feedback to improve performance, whereas others did not.…”
Section: Assessment Reportingmentioning
confidence: 99%
“…Boscardin and colleagues' 12 tips to promote successful development of a learner performance dashboard provides excellent guidance. 7 There were lessons learned during ... it is important to pay attention to the alignment with the construct of competency and to engage stakeholders ...…”
Section: Recommendations For Cbme Assessment Data Visualisationmentioning
confidence: 99%